Effectiveness of Clove (Syzygium aromaticum) Decoction Against Streptococcus mutans on Heat-Polymerized Acrylic Resin - Elin Hertiana; Defta Saputra; Fransiska Nuning; Susi R. Puspitadewi (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Heat-polymerized acrylic resin is the most widely utilized material for removable denture bases. However, its inherent porosity and surface roughness facilitate the accumulation of plaque and bacteria, notably Streptococcus mutans. Poor denture hygiene can lead to mucosal inflammation known as denture stomatitis. Clove plants contain bioactive compounds such as alkaloids, flavonoids, terpenoids, phenolics, and essential oils, which possess established antibacterial properties. This study aimed to evaluate the effectiveness of clove flower and leaf decoctions against Streptococcus mutans on heat-polymerized acrylic resin. Materials and Methods: This laboratory experimental study employed a post-test only control group design. Twenty-seven heat-polymerized acrylic resin plates (10 x 10 x 2 mm) were divided into three groups. Group 1 was immersed in 20% clove flower decoction, Group 2 in 20% clove leaf decoction, and Group 3 in distilled water (control), each for 15 minutes. Results and Discussion: Significant differences in Streptococcus mutans counts were observed between the clove flower decoction group compared to the clove leaf decoction group (p = 0.025) and the distilled water group (p = 0.001). No significant difference was found between the clove leaf decoction and distilled water groups (p = 0.415). Conclusion: Clove flower decoction is significantly more effective in inhibiting the growth of Streptococcus mutans compared to clove leaf decoction.